PENGADAAN PERUMAHAN SKALA MENENGAH DI DENPASAR: STUDI BERDASARKAN STRATEGI PENGEMBANG - Juliastika, Dewa Ngakan Made; Widya Paramadhyaksa, I Nyoman; Trimarianto, Ciptadi (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 3 No 3 (2016): Oktober 2016DO - 10.24843/JRS.2016.v03.i03.p08, 2016)
In Denpasar, demands for housing are increasing rapidly and creating a potential economic opportunity in housing development. Since housing is seldom provided by the state, its provision relies heavily on developers, who, to date, have successfully delivered various housing types as well as competitive marketing strategies to attract more consumers. But problems occur when developers focus more on generating profits than conforming to the housing development guidelines and policies that have been established. Taking this situation as a point of departure, this paper suggests seven sets of strategies implemented by various developers at seven different housing developments. Utilizing qualitative research methods, the study has identified three important strategies in the development of medium-scale housing by developers in Denpasar, including: (1) those used during pre-construction; (2) those implemented during  the construction phase; and those applied in the aftermath of sales post-construction. All three strategic groupings of strategies are the basis for developing the characteristics of medium-scale housing delivery in Denpasar. Keywords: housing delivery; strategy of housing development; developer Abstrak Pertambahan penduduk di kota Denpasar menyebabkan peningkatan permintaan akan kebutuhan perumahan,sehingga pihak swasta, khususnya developer, berupaya mengembangkan perumahan dengan berbagai tipe. Adanya persaingan antar pengembang dalam pengadaan perumahan memunculkan berbagai konsep strategi untuk menarik calon pembeli. Permasalahan yang sering terjadi adalah pihak pengembang kurang memperhatikan ketentuan-ketentuan yang berlaku dalam mengembangkan perumahan yang sudah diatur pada kebijakan-kebijakan terkait pengadaan perumahan. Penelitian ini menggunakan metode kualitatif induktif. Lokasi penelitian terletak di Kota Denpasar dengan mengambil tujuh kasus yang mewakili masing-masing kecamatan. Hasil penelitian ini adalah: (1) Konsep pengadaan perumahan skala menengah pada tahap pra konstruksi dan juga tahap konstruksi; (2) Pengelolaan perumahan skala menengah pada tahap pasca konstruksi, yaitu pada tahap purna jual; dan (3) Karakteristik pengadaan perumahan skala menengah di Denpasar. Ketiga hasil penelitian ini ditinjau dari strategi yang dilakukan oleh pengembang. Dialog dilakukan meliputi dialog antar isu di lapangan, serta dialog antara isu di lapangan dengan pemahaman umum secara etik.
Keywords: pengadaan perumahan, strategi pengadaan perumahan, pengembang swasta